2022
DOI: 10.1017/s0714980821000581
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Older Adults Socially Distancing during the Early Stages of the COVID-19 Pandemic

Abstract: During the early stages of the COVID-19 pandemic, individuals were asked to stay home and restrict outings to limit the spread of the virus. Physical isolation was particularly emphasized for older adults over the age of 60 who, because of their age and related medical conditions, were at increased risk of severe disease and death from the virus. This led to reduced spread of the virus but also to social and emotional health challenges for older adults. Protecting the physical health of older adults was of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…7 Further, as COVID-19 continued, older adults became less concerned about their physical safety and more concerned about meeting their social and emotional needs. 8 The lack of prosocial behavior in older adults negatively influenced their quality of life, physical health, and mental health. 4,5,9 Many individuals have used technology, such as Zoom or FaceTime, to cope during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Further, as COVID-19 continued, older adults became less concerned about their physical safety and more concerned about meeting their social and emotional needs. 8 The lack of prosocial behavior in older adults negatively influenced their quality of life, physical health, and mental health. 4,5,9 Many individuals have used technology, such as Zoom or FaceTime, to cope during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The experience of community-dwelling older adults socially distancing during the COVID-19 pandemic in Saskatchewan, Canada, was examined by our research team, and we found increased feelings of anxiety, low mood, and loneliness. 7 Older adults were forced to be more antisocial and missed prosocial activities, such as volunteering or community involvement. 7 Further, as COVID-19 continued, older adults became less concerned about their physical safety and more concerned about meeting their social and emotional needs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation